2018
DOI: 10.1088/1361-648x/aaa6f5
|View full text |Cite
|
Sign up to set email alerts
|

Production, deformation and mechanical investigation of magnetic alginate capsules

Abstract: In this article we investigated the deformation of alginate capsules in magnetic fields. The sensitivity to magnetic forces was realised by encapsulating an oil in water emulsion, where the oil droplets contained dispersed magnetic nanoparticles. We solved calcium ions in the aqueous emulsion phase, which act as crosslinking compounds for forming thin layers of alginate membranes. This encapsulating technique allows the production of flexible capsules with an emulsion as the capsule core. It is important to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 46 publications
(81 reference statements)
1
16
0
Order By: Relevance
“…Figure 5 shows the expected linear dependence of ∆D from the parameter ∆(∆ρω 2 R 3 0 ) according to eq 9. The deviations at higher rotation frequencies are caused by water leakage from the capsule, which was also observed in previous studies [32]. For the calculation of the elastic moduli, the slope ∆D/∆(∆ρω 2 R 3 0 ) is determined from the initial linear regime (blue curve in Figure 5).…”
Section: A Mechanical Characterization Of the Capsule Shellsupporting
confidence: 64%
See 2 more Smart Citations
“…Figure 5 shows the expected linear dependence of ∆D from the parameter ∆(∆ρω 2 R 3 0 ) according to eq 9. The deviations at higher rotation frequencies are caused by water leakage from the capsule, which was also observed in previous studies [32]. For the calculation of the elastic moduli, the slope ∆D/∆(∆ρω 2 R 3 0 ) is determined from the initial linear regime (blue curve in Figure 5).…”
Section: A Mechanical Characterization Of the Capsule Shellsupporting
confidence: 64%
“…The capsules are washed with water to stop the polymerisation and placed in saturated sodium alginate solution. This lowers the elastic moduli of alginate systems and thus lead to capsules that are easier to deform [32]. For mechanical characterization of the capsule shells we use two methods, compression between parallel plates and deformation in a spinning drop apparatus.…”
Section: B Preparation Of Capsulesmentioning
confidence: 99%
See 1 more Smart Citation
“…This swelling process would be considerably favored in presence of sodium salt compare to distilled water in particular due to the competition of sodium and calcium ions for the guluronic acid residues on alginate chains favoring the large decrease of cross-linking density in the alginate network and the huge increase of water uptake within the membrane. Authors recently clearly demonstrated, using spinning drop techniques, capsule squeezing experiments and interfacial shear rheology, changes in the mechanical properties of alginate membrane after storage of capsules in calcium or sodium salt solutions [38]. For instance, surface Young modulus determined by compression experiments decreased from 41 to 6.0 N/m when capsules were stored in calcium and sodium salt solutions, respectively.…”
Section: Effect Of Cation Concentrationmentioning
confidence: 99%
“…IV). For a typical ferrofluid-filled capsule with χ = 21, R 0 = 1 mm [21,69], and γ = 0.01 N/m, these Bond numbers correspond to magnetic field strengths H between 0 and about 500 kA/m (or fields B = µ 0 H between 0 and 0.5 T). We consider dimensionless Young moduli Y 2D /γ from 10 −2 (nearly no elasticity) to 100 (elastically dominated) and the purely elastic limit Y 2D /γ = ∞ (where the definition of B m is not useful anymore).…”
Section: E Control Parameters and Non-dimensionalizationmentioning
confidence: 99%